2003
DOI: 10.1007/s10067-003-0716-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of imatinib mesylate (STI571) treatment for a patient with rheumatoid arthritis developing chronic myelogenous leukemia

Abstract: We report on an 80-year-old man with rheumatoid arthritis (RA) who presented with chronic myelogenous leukemia (CML). Five years after the onset of RA, the CML diagnosis was made. The patient was treated for CML with 300 mg of imatinib mesylate (STI; signal transduction inhibitor 571) for 8 weeks. Laboratory tests showed that the C-reactive protein level, percentage of cells exhibiting the Philadelphia chromosome (Ph1), WBC count, and Lansbury index for RA all dropped respectively from 7.5 mg/dl to 1.0 mg/dl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 9 publications
4
45
1
Order By: Relevance
“…Imatinib efficiently prevented disease and induced remission in an autoimmune arthritis model (13,14) and ameliorated autoimmune nephritis in a mouse model of lupus (15). These data are consistent with case reports and phase I studies in humans demonstrating a positive effect of imatinib on rheumatoid arthritis (16,17), psoriasis (18), spondyloarthritis (19), and Crohn's disease (20).…”
supporting
confidence: 82%
“…Imatinib efficiently prevented disease and induced remission in an autoimmune arthritis model (13,14) and ameliorated autoimmune nephritis in a mouse model of lupus (15). These data are consistent with case reports and phase I studies in humans demonstrating a positive effect of imatinib on rheumatoid arthritis (16,17), psoriasis (18), spondyloarthritis (19), and Crohn's disease (20).…”
supporting
confidence: 82%
“…An early hint that imatinib mesylate might be effective in non-oncologic conditions came in 2003, when Japanese investigators reported the case of an 80-year-old man with rheumatoid arthritis (RA) who developed chronic myelogenous leukemia, for which he was treated with imatinib mesylate. Not only did his chronic myelogenous leukemia improve, but the RA also was suppressed, and the authors speculated that the effect could be related to inhibition of PDGF signaling in rheumatoid fibroblasts (16). Along the same lines, investigators from 2 different laboratories have recently reported in vitro inhibition of PDGF proliferation in rheumatoid synovial fibroblasts with imatinib mesylate treatment at doses of Յ1 g (17,18), also suggesting its potential for use in RA.…”
mentioning
confidence: 98%
“…Imatinib also exerts potent immunomodulatory effects in vitro and in vivo 1 . Recent reports described the efficacy of imatinib in treating patients with various autoimmune and inflammatory diseases such as rheumatoid arthritis (RA), systemic scleroderma, pulmonary arterial hypertension, and lupus nephritis [2][3][4][5] .…”
Section: To the Editormentioning
confidence: 99%